Emerging role of natural products in cancer immunotherapy - Songtao Dong; Xiangnan Guo; Fei Han; Zhonggui He; Yongjun Wang (Elsevier, 2022)
Cancer immunotherapy has become a new generation of anti-tumor treatment, but its indications still focus on several types of tumors that are sensitive to the immune system. Therefore, effective strategies that can expand its indications and enhance its efficiency become the key element for the further development of cancer immunotherapy. Natural products are reported to have this effect on cancer immunotherapy, including cancer vaccines, immune-check points inhibitors, and adoptive immune-cells therapy. And the mechanism of that is mainly attributed to the remodeling of the tumor-immunosuppressive microenvironment, which is the key factor that assists tumor to avoid the recognition and attack from immune system and cancer immunotherapy. Therefore, this review summarizes and concludes the natural products that reportedly improve cancer immunotherapy and investigates the mechanism. And we found that saponins, polysaccharides, and flavonoids are mainly three categories of natural products, which reflected significant effects combined with cancer immunotherapy through reversing the tumor-immunosuppressive microenvironment. Besides, this review also collected the studies about nano-technology used to improve the disadvantages of natural products. All of these studies showed the great potential of natural products in cancer immunotherapy.